Marketing Strategies in Sharia Hospitals in Indonesia: A Systematic Literature Review - Okwandi, Arwin; Soeprijadi, Boby; Revai, Doni; Efawati, Yen (PT Wahana Global Education, 2026)
Abstract: This study aims to systematically review value-based and patient-centered marketing strategies in Sharia hospitals and to develop an integrated conceptual framework grounded in Islamic marketing principles. A systematic literature review was conducted following PRISMA guidelines using Scopus, Web of Science, PubMed and Google Scholar databases. A total of 30 peer-reviewed articles published between 2014 and 2026 were selected and analysed using thematic synthesis. The findings indicate that effective marketing strategies in Sharia hospitals are driven by the integration of value-based healthcare, patient-centered care and Islamic ethical principles. Digital marketing and relationship marketing further enhance patient engagement, trust and long-term loyalty. The study is limited by the availability of empirical studies focusing specifically on Sharia hospitals. Future research should empirically validate the proposed framework. Hospital managers should integrate Islamic values into marketing strategies, improve patient experience and leverage digital platforms to enhance engagement. This study provides a novel integrated framework linking Islamic marketing, value-based healthcare and patient-centered care in the context of Sharia hospitals.